2020
DOI: 10.7475/kjan.2020.32.1.98
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model Explaining the Health Behaviors among Adults with Metabolic Syndrome: Theory of Planned Behavior Approach

Abstract: This study aimed to identify the factors explaining the performance of health behaviors among adults with metabolic syndrome based on the theory of planned behavior. Methods: A total of 218 adults with metabolic syndrome were recruited for the study from September to December, 2017. Data were analyzed using SPSS/WIN 22.0 and AMOS 24.0. Results: The hypothetical model appeared to fit the data with x 2 /df=2.65, SRMR (Standardized Root Mean Residual)=.07, PNFI (Parsimonious Normed Fit Index)=.67. Attitude toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Findings reported in the literature were partially supported by our study results and somewhat inconsistent. For example, in using the TPB to investigate intention and health behaviors among those at high risk of or having metabolic syndrome, Jang and Song (2020) reported that attitude, subjective norm, and PBC all influenced intention regarding health behaviors. In a similar assessment of individuals with obesity (body mass index > 30 kg/m 2 ), Chevance et al (2017) reported that, although attitude, subjective norm, and PBC influenced intention for both physical activity and eating behaviors, the actual health behaviors were affected by different TPB constructs; specifically, attitude, PBC, and intention influenced physical activity, whereas subjective norm and intention influenced eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings reported in the literature were partially supported by our study results and somewhat inconsistent. For example, in using the TPB to investigate intention and health behaviors among those at high risk of or having metabolic syndrome, Jang and Song (2020) reported that attitude, subjective norm, and PBC all influenced intention regarding health behaviors. In a similar assessment of individuals with obesity (body mass index > 30 kg/m 2 ), Chevance et al (2017) reported that, although attitude, subjective norm, and PBC influenced intention for both physical activity and eating behaviors, the actual health behaviors were affected by different TPB constructs; specifically, attitude, PBC, and intention influenced physical activity, whereas subjective norm and intention influenced eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Ajzen formulated the TPB to offer a theoretical framework for determining factors that influence decision-making about behavior as well as for predicting behavior. It has been widely applied to individual behaviors, including health behaviors such as exercise and eating habits (Brooks et al, 2017; Fishbein & Ajzen, 2010; Genrich et al, 2020; Jang & Song, 2020). Thus, this study’s specific objectives were to (a) identify specific TPB constructs influencing intention and HPB in high-risk workers and (b) differentiate between intention and specific HPB exhibited by workers according to the number of metabolic syndrome risk factors present.…”
mentioning
confidence: 99%
“…Higher scores indicate a more positive attitude toward health behaviors. The original study reported a Cronbach’s ⍺ of 0.91, 40 while Jang and Song 41 reported a Cronbach’s ⍺ of 0.86. In this study, Cronbach’s ⍺ was 0.93.…”
Section: Methodsmentioning
confidence: 98%
“…Attitudes toward physical activity were measured using an instrument developed by Boudreau and Godin 40 and adapted by Jang and Song. 41 The instrument consists of eight items rated on a 7-point Likert scale. Higher scores indicate a more positive attitude toward health behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Nursing theories are fundamentally focused on patient care, and their usefulness in the nursing profession is clear. Although the TPB originated in the domain of social psychology, it has been used in clinical nursing settings for patients with metabolic syndrome 14 and type 2 diabetes 15 as well as to develop a protocol for an educational program for patients with type 2 diabetes. 16 Given the fact that the TPB has been applied in nursing research and practice, the authors believe that it is worthwhile to analyze and evaluate it as a borrowed theory using a framework designed for nursing theory and to characterize its potential value for the development of nursing science.…”
Section: What This Article Addsmentioning
confidence: 99%